2018
DOI: 10.1111/bjd.16557
|View full text |Cite
|
Sign up to set email alerts
|

Surgical re-excision vs. observation for histologically dysplastic naevi: a systematic review of associated clinical outcomes

Abstract: Based upon the available evidence the rates of biopsy-site primary melanoma were similarly low among observed lesions and re-excised lesions. This suggests that HDNs can be observed with minimal adverse melanoma-associated outcomes. However, all included articles were of low quality and further prospective trials could better guide clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Opinion is divided regarding their definition, histological grading, clinical significance and risk of subsequently developing cutaneous melanoma (CM). A recent systematic review by Vuong et al 1 evaluated the outcomes of observed versus re-excised histologically confirmed DN, with data largely drawn from North American centres. The recent multicentre study by Kim et al 2 helped to further elucidate the risk of subsequent cutaneous melanoma in patients with DN and guide pragmatic management of moderately severe DN, but there remains a lack of overarching consensus guidance for clinicians and a notable paucity of outcome data in the United Kingdom.…”
Section: Dear Editormentioning
confidence: 99%
“…Opinion is divided regarding their definition, histological grading, clinical significance and risk of subsequently developing cutaneous melanoma (CM). A recent systematic review by Vuong et al 1 evaluated the outcomes of observed versus re-excised histologically confirmed DN, with data largely drawn from North American centres. The recent multicentre study by Kim et al 2 helped to further elucidate the risk of subsequent cutaneous melanoma in patients with DN and guide pragmatic management of moderately severe DN, but there remains a lack of overarching consensus guidance for clinicians and a notable paucity of outcome data in the United Kingdom.…”
Section: Dear Editormentioning
confidence: 99%
“…These findings further add to the growing body of evidence that clinical observation is a reasonable strategy to managing dysplastic nevi, even those with moderate dysplasia and positive histologic margins. 12 The data from Kim et al 11 are a welcome addition to the relative paucity of evidence-based literature to guide the management of dysplastic nevi. However, clinicians must interpret these results in the context of the study design.…”
mentioning
confidence: 99%
“…To address the utility of DN re‐excision, Vuong et al . conducted a thorough and comprehensive systematic review, analysing all published data on the development of primary cutaneous melanoma at biopsy sites of DN . They sought to analyse differences in melanoma occurring in biopsy‐proven DN managed with re‐excision vs. observation.…”
mentioning
confidence: 99%
“…They found 11 total melanomas: five in 1138 re‐excised DN (0·44%) and six in 1535 observed DN (0·39%). Of the melanomas arising in observed DN, five of the six were initially only partially biopsied, signifying potential sampling error . Their data suggest that there is a similarly low likelihood of melanoma development in biopsy‐proven DN managed with re‐excision or observation and also underscores the risk of missing a melanoma in partial biopsies of atypical melanocytic lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation